2006
DOI: 10.1007/s11160-006-9013-y
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis in the spotted ray Torpedo marmorata

Abstract: Investigation of embryos, neonates, sub-adult and adult female Torpedo marmorata showed that oogenesis is immediate. It begins very early in development and continues, in its proliferative phase after birth. In newborns, 3-4 month old, all germ cells present in the ovary have achieved diplotene stage and are surrounded by a single layer of small follicle cells (primordial follicles). Later with continued oocyte growth, the follicular epithelium (granulosa) progressively changes its organization and becomes mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…The basic organization of the ovary in S. bonapartii is similar to that seen in other Batoids (Prisco et al, 2007;Díaz Andrade et al), so as their relationship with the epigonal organ during sexual development (Koob & Callard, 1999;Galíndez & Aggio, 2002, Storrie). The features of the ovary in this species agree with the "external" type defined by Pratt (1988).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The basic organization of the ovary in S. bonapartii is similar to that seen in other Batoids (Prisco et al, 2007;Díaz Andrade et al), so as their relationship with the epigonal organ during sexual development (Koob & Callard, 1999;Galíndez & Aggio, 2002, Storrie). The features of the ovary in this species agree with the "external" type defined by Pratt (1988).…”
Section: Discussionmentioning
confidence: 60%
“…In spite of the evolutionary and economic importance of chondrichthyans, there are a scarce number of investigations with regards to the ovary structure and they were performed mainly in species from intensive fishing zones (Pratt, 1988;Chatchavalvanich & Visuttipat, 1997;Hamlett & Koob, 1999;Andreuccetti et al, 1999;Prisco et al, 2001Prisco et al, , 2002aPrisco et al, , 2002bPrisco et al, , 2007Storrie, 2004;Barone et al, 2007). Only one reference exists about the ovary from species of the genus Sympterygia (Díaz Andrade et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In other species of batoids such as Torpedo marmorata (Prisco et al, 2001) Cell inclusions in the form of yolk granules and the vacuolated appearance of the cytoplasm (probably due to lipid content) of follicular cells of oocytes in P. magdalenae might correspond to precursors of yolk and steroids which contribute to the oocyte growth, as described by Tsang and Callard (1983) and Prisco et al (2002aPrisco et al ( , 2007. These inclusions are similar in U. halleri (Babel, 1967), U. jamaicensis Additionally, the follicular cells of elasmobranchs, including P. magdalenae, have extensions that allow the transport of these precursors to the oocyte (Lutton et al, 2005), such as the intercellular bridges (Prisco et al 2002b(Prisco et al , 2007Barone et al 2007;D ıaz-Andrade et al 2009D ıaz-Andrade et al , 2011 and transosomes . However, in P. magdalenae it was not possible to determine the type of these extensions.…”
Section: Microscopic Analysismentioning
confidence: 77%
“…Similarly, material transport and cell extensions have also been observed in other vertebrates including some birds and squamate reptiles (Press, ; Rahil and Narbaitz, ; Motta et al, ; de Caro et al, ). Andreuccetti et al () and Prisco et al () suggested that this feature may be advantageous in species with oocytes provided almost entirely with yolk and a small germ disc (telolecithal egg), as is the case in elasmobranchs (Wyffels, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the material employed for this work was stored in cold chambers for several days, so that structural details may have not been correctly preserved, making difficult an accurate conclusion. Like other Chondrichthyans (Prisco et al, 2007), Z. chilensis exhibits a double theca. The connective nature of the inner one and the high vascularization at the beginning of vitellogenesis leads to assume that is involved in the transport of yolk precursors.…”
Section: Discussionmentioning
confidence: 93%